Operational Parameters Assessment of a Biomass-To-Fuel Gas Converter - Chong, K.H; Law, P.L; Rigit, A.R.H.; Baini, R.; Saleh, S.F; Awangku Yussuf, A.A.R (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study presents the assessment on the existing mini-sized biomass-to-fuel gas (B2F) converter. Operational parameters, such as composition of after filtered residual liquid (AFRL), composition of raw combustible fuel gases produced using wood chips and coal as feedstock, and nearby incremental levels of carbon monoxide and suspended particulate during operation, are determined. Analysis results of the raw (unburnt) combustible fuel gases from low grade Balingian-Mukah coal and wood chips found that there were approximately 23-29% gasoline constituents; 15-30% diesel constituents; 1-16% CO2; 10-13% O2, CO, SO, NO and H2O; 46-71% combustible gases. It was observed that the phenol contained in the AFRL recorded approximately 5,310 mg/L. Moreover, by-products, such as 1.5% tars and 13% AFRL, were produced. The result shows that a B2F converter is suitable to harvest the combustible gases that can be used as fuel for internal combustion engines. However, the amount of organics indicated that the AFRL should not be discharged directly into watercourses without pre-treatment.